Domination without dominance: Inca-Spanish encounters in early colonial Peru - Lamana Ferrario, Gonzalo (Latin America otherwise : languages, empires, nations, 2008)
Introduction : situated interventions : colonial imprints, decolonial moves -- Beyond exotization and likeness : alterity and the production of sense in a colonial encounter -- Christian realism and magicality during Atahualpa's imprisonment -- Why betting a barrel of preserves can be a bad thing to do : civilizing deeds and snags -- Illusions of mastery : Manco Inca's war and the colonial normal -- The emergence of a new Mestizo consciousness : an unthinkable Inca -- Power as moves : a mid-1540s repertoire of flipping the coin -- The end -- Basic political chronology of the Spanish conquest